EDITORIAL - Ordonez, J. C. (Revista de Engenharia Térmica, 2013)
I would like to direct the attention of the reader to thermal energy storage. Increased interest in on-site renewable power generation mainly through direct energy conversion using photovoltaic systems together with policy changes in support of “net-zero energy” buildings are bringing a new wave of interest on energy storage. Despite the progress seen in electrochemical storage, cost, cyclability and life-time remain as major hurdles to be overcome. This confluence of need for energy storage and lack of robust solutions opens an opportunity for a renewed look at thermal energy storage. This is a field, in which problems are by nature dynamic and one in which interesting mathematical problems arise (e.g. phase change, interface tracking). It is also a field that continues to serve as a great playground in which to explore advances in applied thermodynamics (e.g construtal theory, entropy generation minimization) and one that reminds us clearly of the goal of making the best possible with the available energy and exergy at our disposal.